Functional measurement of canine muscular fitness: refinement and reliability of the Penn Vet Working Dog Center Sprint Test - Farr, Brian; Gabrysiak, Jorie; Traylor, Rosemary; Zayas, Sofia; Ramos, Meghan; Mallikarjun, Amritha; Otto, Cynthia (Frontiers in Veterinary Science, 2023)
Working, sporting, and companion dogs require muscular fitness to perform their daily tasks, competitive activities, and operational functions effectively and with a low risk of injury. There are currently no methods to measure the muscular fitness of dogs who are not debilitated. Sprint performance is highly correlated with muscular fitness in humans, and various sprint assessments are used to measure performance for sporting and tactical athletes. The Penn Vet Working Dog Center Sprint Test (ST) is a 25 m maximal effort sprint from a down position and was developed to be a low-cost measure of muscular fitness suitable for field use. The purpose of this project was to describe the refinements to the ST, detail the performance and measurement protocol, evaluate the measurement inter-rater and intra-rater reliability, characterize the acceleration profile, and explore the inter-day reliability. Both naïve and experienced raters demonstrated excellent intra-rater and inter-rater reliability. The acceleration profile of the dogs in this study was similar to that of average adult human sprinters and demonstrated the role of muscular fitness in performance over this short distance. Finally, a small group of dogs showed moderate inter-day reliability and provided initial performance data to inform future studies. The ST appears to be a reliable measure of canine muscular fitness and could be used to assess performance in healthy dogs and guide the return to sport or work of debilitated dogs.